PENGARUH TOP OF MIND, BRAND RECALL, DAN BRAND RECOGNITION TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI SAYURBOX BALI - La Ode Marsudin; Saortua Marbun (Journal Research of Management, 2023)
The objective of this study was to examine the impact of three variables - Top of Mind, Brand Recall, and Brand Recognition - on consumer purchasing decisions in Sayurbox Bali. Multiple linear regression analysis was conducted using a sample of 100 randomly collected data from Sayurbox Bali consumers. The findings revealed that Brand Recall exerted a significant influence on consumer purchasing decisions, with a t-value of 4.126 and a p-value of <0.001. Conversely, Top of Mind and Brand Recognition did not demonstrate a significant impact on consumer purchasing decisions, as evidenced by respective t-values of 1.966 and 1.233, and p-values of 0.052 and 0.221. Consequently, it can be inferred that Brand Recall emerges as the most crucial factor influencing consumer purchasing decisions in Sayurbox Bali. To enhance brand recall among consumers, the company is advised to intensify and sustain marketing promotions and campaigns. Additionally, improving product quality and services to uphold and enhance customer satisfaction is recommended. However, focusing excessively on the variables of Top of Mind and Brand Recognition is unnecessary, as they do not significantly influence consumer purchasing decisions.